The Effect of Acupuncture Therapy on Reducing Blood Pressure in Patients with Hypertension of Liver Hyperactivity Syndrome - Irawan, Teddy; Ningrum, Anis Lupita; Aditya, Stefanus; Xaverius, Franciscus (Jurnal Sehat Indonesia (JUSINDO), 2025)
Hypertension is one of the leading causes of death worldwide, accounting for approximately 7.5 million deaths annually. In Indonesia, the prevalence of hypertension has shown an increasing trend over the years. According to the 2018 Basic Health Research (Riskesdas), 34.1% of the Indonesian population suffers from hypertension. Hypertension is a pathophysiological condition characterized by elevated blood pressure above the normal limit of 120/80 mmHg. Acupuncture therapy has been shown to lower both systolic and diastolic blood pressure in patients with Liver Yang Hyperactivity Syndrome-related hypertension. This study aims to determine the effect of acupuncture therapy on blood pressure reduction in patients with hypertension due to Liver Yang Hyperactivity Syndrome. This research used a quantitative approach with a pre-experimental design, specifically a one-group pre-test and post-test design. A total of 20 participants were selected through purposive sampling at the Sumber Sehat Acupuncture Foundation, Bandung, from March to June 2025. The sample consisted of individuals aged 40–60 years who underwent four sessions of acupuncture therapy over four consecutive days. Blood pressure was measured before and after the treatment period. Statistical analysis showed a significant decrease in systolic blood pressure, from an average of 153 mmHg to 130 mmHg (p = 0.000), and in diastolic pressure, from 87 mmHg to 75 mmHg (p = 0.000), following acupuncture therapy. Traditional Chinese Medicine, particularly acupuncture, is statistically proven to significantly reduce blood pressure in patients with hypertension. Therefore, acupuncture can be considered a complementary alternative in hypertension management.